Performance Evaluation of Agricultural Extension Officers in Kolaka District, Indonesia - Rina Astarika; Adrian Tawai; La Ode Nafiu; La Ode Muh. Munadi; Muhammad Amrullah Pagala; Deki Zulkarnain (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Agricultural extension workers have the task of encouraging farmers to change their way of thinking, working and living in accordance with the times and agricultural technology. The study has the objective of evaluating the performance of agricultural extension workers in accordance with the Regulation of the Minister of Agriculture of the Republic of Indonesia No. 91/Permentan/OT.140/9/2013 Regarding Guidelines for Performance Evaluation of Agricultural Extension Officers which was carried out from April to September 2022.  This study uses qualitative methods to describe and examine the results of interviews and observations of selected respondents to obtain more accurate information. The research informants are 12 agricultural extension workers at the Kolaka Regency Agriculture Office. The results of the research from 12 agricultural extension workers had many obstacles, especially skills and experience in terms of extension preparation, implementation of extension, evaluation, and reporting in accordance with the Regulation of the Minister of Agriculture no. 91/Permentan/OT.140/9/2013. The findings refer to the Regulation of the Minister of Agriculture No. 91/Permentan/OT.140/9/2013 is the first step for local, provincial and government governments of the Republic of Indonesia to re-evaluate the performance of agricultural extension workers in all regions.